Intellectual property strategies and firm growth : evidence from Finnish small business data - Heikkilä, Jussi (2012)
The goal of this study is to shed light on the relationship between intellectual property (IP) strategies and firm growth. In brief, IP strategies are means of capturing returns on innovation investments. Employment effects and sales growth effects of innovations have been studied extensively in both theoretical and empirical economic literature but prior research has seldom included IP strategies into the analysis. There is little knowledge, whether there exists growth rate differences among firms that use different IP strategies and do patenting firms effectively demonstrate stronger growth than their non-patenting counterparts. Present study considers IP strategies as potential firm growth determinants.